0998 Sleep-dependent Memory Consolidation In Early Course Schizophrenia Patients And Familial High-risk Relatives. (27th April 2018) - Denis, D; Sato, E; Larson, O; Kohnke, E J; Parr, E; King, J; Stewart, K; Baran, B; Keshavan, M; Manoach, D; Stickgold, R
Abstract: Introduction: Accumulating evidence suggests that sleep-dependent memory consolidation is impaired in schizophrenia. The majority of this research however has focused on chronically medicated patients, making it hard to rule out medication effects. Here, we investigate sleep-dependent memory consolidation in early-course, minimally medicated patients and, for the first time, in relatives of schizophrenia patients. Methods: Participants were 13 early course psychosis patients (9 schizophrenia (SZ), 4 schizoaffective disorder and other psychoses (nSZ)), 14 first-degree relatives of patients with schizophrenia (FHR) and 16 healthy controls (HC). Sleep-dependent memory processing on two different tasks were investigated. The well-characterized finger tapping motor sequence task (MST) was used to investigate procedural memory consolidation. Based on prior studies, we expected reduced overnight improvement of task performance in SZ and FHR. A word pairs task (WPT) was used to investigate sleep-dependent declarative memory consolidation, which is also impaired in SZ. We expected SX and FHR to show more overnight forgetting, compared to HC. Results: On the MST, patients showed slower typing. In terms of overnight improvement, HC, FHR, and nSZ showed similar improvement (13–22%), while SZ only showed 3% ( p = .05, SZ vs all other groups). With regards to the WPT, HC and nSZ showed similarly small overnight forgetting (0 and 3%), while FHR and SZ showed significantly more forgetting (11 and 16%; p = .03). Age and sex were similar across groups. Conclusion: These results suggest impaired sleep-dependent procedural memory consolidation in early course schizophrenia patients, not present in those with a non-schizophrenia diagnosis. Furthermore, on a declarative task, relatives of schizophrenia patients showed impairment similar to the schizophrenia patients. Study of additional subjects is ongoing. Analyses correlating this behavioral results with deficits in sleep spindles - a proposed endophenotype for schizophrenia - will be presented. Support (If Any): NIH grants MH107579 and MH044832.